PENDEKATAN PERSUASIF GURU PENDIDIKAN AGAMA ISLAM DALAM MENGATASI GANGGUAN BELAJAR AKIBAT PENGGUNAAN GADGET BERLEBIHAN PADA SISWA KELAS V SD NEGERI 112 BUTON - Waode Hartin; Madi; Basri (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to describe the implementation of the persuasive approach used by Islamic Religious Education (PAI) teachers in addressing learning disturbances caused by excessive gadget use among fifth-grade students at SD Negeri 112 Buton, as well as to identify the supporting and inhibiting factors in its implementation. The rapid development of digital technology has led to increased gadget use among elementary school students, which often negatively affects students’ learning concentration, motivation, and classroom discipline.This research employed a qualitative descriptive approach. Data were collected through observation, interviews, and documentation. The subjects of the study were Islamic Religious Education teachers and fifth-grade students at SD Negeri 112 Buton. The data were analyzed through data reduction, data display, and conclusion drawing.The results show that PAI teachers implemented a persuasive approach through several strategies, including providing religious and educational advice, individual communication, learning motivation, and discipline reinforcement through class agreements. These strategies contributed positively to students’ behavioral changes, particularly in reducing excessive gadget use and improving learning concentration.Furthermore, the supporting factors of this approach include good teacher-student relationships, students’ awareness of class rules, a conducive school environment, and teacher role modeling. Meanwhile, the inhibiting factors include excessive gadget use outside school, lack of parental supervision, students’ established habits, and peer environmental influence.In conclusion, the persuasive approach implemented by PAI teachers is considered fairly effective in addressing students’ learning disturbances, although it still requires strong support from family and social environments to achieve optimal results.